Peranan Filsafat Hukum Dalam Kehidupan Berpancasila - Budiman, Andri (HUMANIORUM, 2024)
In general, Pancasila is used as the Nation's philosophy of life, State Ideology and State Foundation as well as being used as the source of all sources of law. It is a must to be used as a guideline and must be implemented by every component of citizens living within the framework of the Unitary State of the Republic of Indonesia.It is said to be the nation's philosophy of life because all the important points contained in Pancasila are a form of crystallization of all the diversity of culture, religion, ethnicity, civilized values ​​that have lived and developed for generations and centuries in Indonesian society and all Other forms of differences can be accumulated in one very philosophical value, namely Pancasila. Based on the description above, the formulation of the problem is as follows: 1. How is legal philosophy related to Pancasila? 2. How to apply legal philosophy and Pancasila values ​​in life ? The necessity of making laws based on Pancasila as the nation's ideology is because the nation's ideology is the basis of the State's philosophy. This shows that in fact laws in Indonesia are not simply exported from one country to another, because every law that applies to a nation is a reflection of the values ​​and morals of that nation. Laws can be enforced if the law is in accordance with the values ​​of the nation itself. So laws that are effectively implemented are laws that are based on the values ​​of the nation itself.Legal philosophy is related to Pancasila as a philosophy of law formation in Indonesia and also as a guideline for life for the nation and state. Plays an important role in laying the basis for philosophical legal values ​​which are able to realize the ideals of justice, benefit and certainty in society.